VARIASI MORFOLOGI POLEN GENUS GLOBBA (ZINGIBERACEAE) DI SUMATRA BARAT - Syamsuardi; Mansyurdin; Nurainas; Tri Susanti (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
Pollen morphology of nine taxa of Globba (Globba leucantha, G. patens, G. variabilis, G. hasseltii,, G. fecunda, G. atrosanguinea, G. aurantiaca, G. multifolia dan G. Paniculata) that collected from various fields in the regions of West Sumatra were examined. Four diagnostic characteristics (pollen types, shapes, apertures and ornamentations) were examined and photographed by scanning electron microscopes (SEM). There was variation of pollen characteristics between nine species of West Sumatran Globba. The pollen shape of five Globba species (G. leuchanta, G. fecunda, G. atrosanguinea) was oblate. The spheroidal shapes were detected at G. variabilis, G. hasseltii dan G. multifolia. The unique prolete shape only detected at Globba patens. For aperture characteristics, the existence aperture were detected at pollens of four species (G. leuchanta, G. patens, G. atrosanguinea and G. aurantiaca) but was not detected at pollens of G. variabilis, G. hasseltii G. fecunda, G. multifolia, and G. paniculata. Four types of exine ornamentation characters were detected namely: echinate-retikulate at G. leuchanta, G. fecunda, and G. atrosanguinea; echinate-granulate at G. patens, G. hasseltii, G. multifolia, G. aurantiaca, and unique echinate-perforate and echinate-psilate were detected at G. variabilis and G. paniculata, respectively. All nine West Sumatran Globba species have the spina with variation in length (1.17 to 2.10 μm). These palynological data appear to be informative and useful for distingusing among species of Globba and for elucidating among Globba species.